Introduction of a novel freshwater species Setoseptoria guangxiensis sp. nov., with Setoseptoria baiyunensis nom. nov., in Lentitheciaceae, Pleosporales - Shu, Yongxin; Senanayake, Indunil C.; Boonmee, Saranyaphat; Doilom, Mingkwan; Dong, Zhangyong; Dong, Wei (Phytotaxa, 2024)
The investigation of freshwater fungal diversity in Guangxi Province, China, reveals an interesting ascomycetous species. The morphological and phylogenetic analyses incorporating combined LSU, SSU, ITS and tef1-α sequence data have identified it as a novel species within Setoseptoria, namely S. guangxiensis. Setoseptoria guangxiensis is distinct within the genus by its uni-loculate ascomata, which have a prominent papilla and lack a clypeus-like structure, as well as 1-septate ascospores that are surrounded by a defined gelatinous sheath. In addition, Setoseptoria baiyunensis nom. nov. is proposed for a collection MHZU 22-0133 as the previous name “Setoseptoria bambusae” is invalidly published. A key to the sexual morph of species within Setoseptoria is provided.